Socio-Demographic Factors Affecting Family Planning Decisions among the Married Women in Rural District of Nepal - Shrestha, Tirtha Man; Gauchan, Shrijana; Aacharya, Ramesh Parsad (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Various socio-demographic factors are known to play decisive role in the acceptance of family planning methods. Commonly known factors include age of the women, age at marriage, age at first pregnancy, education and occupation.Methods: This is a hospital based cross sectional, observational study conducted at Okhaldhunga Community Hospital among married women of reproductive age (15-49 years) attending either general OPD clinic or family planning clinic. Data were collected through an interview using a predesigned questionnaire.Results: Age of women had statistical significance as the acceptance increased with the age. More than two-third of women using methods of family planning were married before the age of 20 years. About 43% of women had first pregnancy before the age of 20 years. There was no statistical significance between the current use of family planning methods and the education (p- value 0.6) and the various occupations (p-value 0.1).Conclusion: There is a need for particular emphasis on contraceptive needs of adolescents and to improve accessibility and availability of all family planning services.